Entrepreneurial Firms and Downstream Alliance Partnerships: Impact of Portfolio Depth and Scope on Technology Innovation and Commercialization Success. (20th January 2013) - Hora, Manpreet; Dutta, Dev K.
<x xml:space="preserve">Abstract</x> To achieve technology innovation and commercialization (TIC) success under complex, protracted, and uncertain product development cycles, entrepreneurial firms engage in downstream alliance partnerships with mainstream industry players. In this study, we examine two specific characteristics of the entrepreneurial firm's downstream alliance portfolio (depth and scope) and their impact on TIC success. Employing a sample of 728 biotech firms and their partnerships with pharmaceutical companies, we find that while portfolio depth and scope separately have positive impact on success, the relationship between portfolio scope and success is additionally moderated by portfolio depth. Further, insights from post hoc interviews also suggest that though it is challenging for entrepreneurial firms to incorporate both depth and scope in alliance partnerships, those that optimally combine both can achieve higher TIC success.